The Qingjiang biota—A Burgess Shale–type fossil Lagerstätte from the early Cambrian of South China - Fu, Dongjing; Tong, Guanghui; Dai, Tao; Liu, Wei; Yang, Yuning; Zhang, Yuan; Cui, Linhao; Li, Luoyang; Yun, Hao; Wu, Yu; Sun, Ao; Liu, Cong; et al. (Science (American Association for the Advancement of Science))
Burgess Shale–type fossil Lagerstätten provide the best evidence for deciphering the biotic patterns and magnitude of the Cambrian explosion. Here, we report a Lagerstätte from South China, the Qingjiang biota (∼518 million years old), which is dominated by soft-bodied taxa from a distal shelf setting. The Qingjiang biota is distinguished by pristine carbonaceous preservation of labile organic features, a very high proportion of new taxa (∼53%), and preliminary taxonomic diversity that suggests it could rival the Chengjiang and Burgess Shale biotas. Defining aspects of the Qingjiang biota include a high abundance of cnidarians, including both medusoid and polypoid forms; new taxa resembling extant kinorhynchs; and abundant larval or juvenile forms. This distinctive composition holds promise for providing insights into the evolution of Cambrian ecosystems across environmental gradients.